2019
DOI: 10.1039/c9ta03163d
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the role of Ni–Fe dual sites in the oxygen evolution reaction based on atomically metal-doped polymeric carbon nitride

Abstract: Ni–Fe dual-metal sites on NiFe-codoped polymeric carbon nitride co-participate in the OER process leading to significantly enhanced electrocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 59 publications
1
72
0
Order By: Relevance
“…The OER kinetics were further analyzed by examining Tafel plots. In another work, the mechanism of active enhancement for Ni–Fe sites was further discussed . The Ni–Fe dual metal sites exhibited a smaller Tafel slope (38 mV dec −1 ) and a lower overpotential (310 mV at 10 mA cm −2 ) when compared to single metal Ni or Fe sites.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 98%
“…The OER kinetics were further analyzed by examining Tafel plots. In another work, the mechanism of active enhancement for Ni–Fe sites was further discussed . The Ni–Fe dual metal sites exhibited a smaller Tafel slope (38 mV dec −1 ) and a lower overpotential (310 mV at 10 mA cm −2 ) when compared to single metal Ni or Fe sites.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 98%
“…23 However, wide applications have been restricted by their inherent defects, such as poor biocompatibility, high cost, low photostability, tedious preparation procedures, and low targeting efficiency toward bacteria. Among these investigated materials, the copper suldes (CuS) 18,19,[24][25][26][27][28][29][30] stand out as suitable choices for photothermal therapy because of their excellent photothermal conversion efficiency in the NIR region and high intrinsic thermal conductivity. [31][32][33] However, the low surface area and easy sedimentation hindered their widely applications in PTT as a means of eliminating trapped bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sun and co-workers developed polymeric carbon nitride (PCN) with atomically dispersed N-coordinated Ni-Fe sites to explore the OER process. [51] Density functional theory calculations based on the oxidized-NiFe@PCN model found that adjacent Ni and Fe atoms coparticipate in the OER process in the NiFe-codoped PCN, thereby leading to a significantly lower energy barrier.…”
Section: The Active Sites For the Oer In Different Nife-based Electromentioning
confidence: 99%